Working with library collections an Introduction for support staff - Keeler, Hali R. 1952- (Library support staff handbooks, 2017)
Working with Library Collections is written in clear language with practical examples of how performance can contribute to exemplary library service. It is aligned with the ALA support staff standards and prepares library support staff to: Know how to use an integrated library system and other appropriate online tools. Know the basic principles of collection development and management. Assist with decisions regarding selection, de-selection, retention and replacement of all types of library resources